Non‐Noble‐Metal Catalyst and Zn/Graphene Film for Low‐Cost and Ultra‐Long‐Durability Solid‐State Zn‐Air Batteries in Harsh Electrolytes. (13th May 2022) - Yang, Xinxin; Zheng, Xuchao; Li, Huanxin; Luo, Bingcheng; He, Yongkang; Yao, Yong; Zhou, Haihui; Yan, Zhanheng; Kuang, Yafei; Huang, Zhongyuan
Abstract: Exploration and development of cost‐effective, ultra‐long durability, and high‐performing non‐noble‐metal catalysts for the oxygen reduction reaction (ORR) to replace Pt‐based catalysts for electrochemical energy conversion devices is still of great challenge. Although several types of non‐noble‐metal catalysts (N‐doped graphene, transition metal nanoparticles, single atomic metal‐nitrogen‐carbon, etc.) are claimed to have comparable or overwhelming catalytic performances compared with commercial Pt/C, their long‐durability, especially in harsh electrolytes, are still unsatisfactory for practical applications. Herein, the classical Fe3 C‐NG catalysts are synthesized and investigated to understand the catalytic and degradation behaviors in Zn‐Air batteries. Experimental analysis and theoretical calculations reveal that the Mott–Schottky heterojunction formed by Fe3 C quantum dots (QDs) and N‐doped graphene carbon (Fe3 C‐NG) boosts the ORR, since the Fe3 C quantum dots provide rapid electron transfer to the valence band of NG. Molecular dynamic simulation suggests that the graphene structure in NG is relatively stable in extremely corrosive electrolyte, which avoids the corrosion of Fe3 C quantum dots. In combination of the Zn/graphene composite film and solid‐state electrolyte, the optimized Zn‐air battery with Fe3 C‐NG catalyst delivers a high open circuit voltage of 1.506 V, high energy density of 706.4 Wh kg –1, and long‐term stability for 1000 h. Abstract : The Fe3 C‐NG Mott–Schottky heterojunction is fabricated to boost the electrochemical activity for oxygen reduction reaction. Experimental results, density functional theory, and molecular dynamic simulations suggest that the Mott−Schottky effect enhances the electrochemical activity for Fe3 C‐NG catalyst, and the graphene layer enables a high stability for the non‐noble‐metal catalyst.